2019
DOI: 10.1001/jamafacial.2018.1197
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors, Causes, and Costs of Hospital Readmission After Head and Neck Cancer Surgery Reconstruction

Abstract: IMPORTANCE Thirty-day hospital readmissions have substantial direct costs and are increasingly used as a measure of quality care. However, data regarding the risk factors and reasons for readmissions in head and neck cancer surgery reconstruction are lacking. OBJECTIVE To describe the rate, risk factors, and causes of 30-day readmission in patients with head and neck cancer following free or pedicled flap reconstruction. DESIGN, SETTING, AND PARTICIPANTS This retrospective, population-based cohort study analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
41
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 34 publications
(74 reference statements)
7
41
2
Order By: Relevance
“…The most common reasons for readmission were infections and wound complications, which is corroborated by prior studies of major ablative head and neck cancer surgery . Given that antibiotic prophylaxis and postoperative wound care practices vary widely among otolaryngologists, this may represent a potential area for quality improvement. Phone calls or other forms of telemedicine follow‐up (i.e., e‐mailing photograph of surgical site) in the early postdischarge period may capture early symptoms or manifestations of infections and wound complications in order to avoid readmission.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The most common reasons for readmission were infections and wound complications, which is corroborated by prior studies of major ablative head and neck cancer surgery . Given that antibiotic prophylaxis and postoperative wound care practices vary widely among otolaryngologists, this may represent a potential area for quality improvement. Phone calls or other forms of telemedicine follow‐up (i.e., e‐mailing photograph of surgical site) in the early postdischarge period may capture early symptoms or manifestations of infections and wound complications in order to avoid readmission.…”
Section: Discussionsupporting
confidence: 61%
“…Our study is the first to calculate the financial strain of readmissions after parotidectomy. Of note, the mean cost per readmission in our study was nearly 12% less than that reported in oropharyngeal cancer surgery ($14,170 per readmission), 21% less than that noted in head‐and‐neck cancer reconstructive surgery ($15,916 per readmission), and 32% less than that accounted in sinonasal cancer surgery ($18,403 per readmission) …”
Section: Discussioncontrasting
confidence: 60%
“…In ensuing randomized phase III trials where cisplatin-radiotherapy (RT) combination was the treatment backbone in control arms, severe toxicity rates ranged between 81.7 and 87.6% (1113). Surgical management of HNC is also complex, with post-operative complications yielding a 19.4% readmission rate within 30 days of reconstruction surgery in referral centers (14). For recurrent and/or metastatic (RM) disease, first-line standard of care (cetuximab combined with platinum−5-fluorouracil doublet) is associated with substantial toxicity (82% incidence of grade 3/4 adverse events) (15).…”
Section: Defining the Context: Why Supportive Care Is Necessary In Hementioning
confidence: 99%
“…[2][3][4] Prior studies performed in North American otorhinolaryngology -head and neck surgery departments seeking to identify risk factors for unplanned hospital readmission among patients undergoing otolaryngology procedures reported rates of hospital readmission ranging from 3.1 to 7.3%. 2,[4][5][6][7][8][9] These studies identified a strong association between the occurrence of postoperative complications and unplanned 30-day readmissions. 2,10 In another study that included 1,058 patients undergoing ear, nose, and throat (ENT) surgery, Graboyes et al found that patients who experienced a complication during or after their index hospitalization were 11.9 times more likely to be readmitted to the hospital within 30 days than patients without complications.…”
Section: Introductionmentioning
confidence: 99%